Geothecnologies in the assessment of land use changes in coffee regions of the state of Minas Gerais in Brazil - Vieira, Tatiana Grossi Chquiloff; Alves, Helena Maria Ramos; Bertoldo, Mathilde Aparecida; Souza, Vanessa Cristina Oliveira de (Coffee Science - ISSN 1984-3909, 1970)
Coffee is one of Brazilian most important cash crops due to the incomes generated by exportation. Southern Minas Gerais State represents approximately half of the total national production, although the greatest expansion of the crop has been observed in the western part of the state (“Triângulo Mineiro” and “Alto Paranaíba” regions). As a requirement for future planning, it is important to establish efficient methodologies to map and monitor these lands, with the possibility of an easier periodical updating of the information. In this work geotechnologies were used to evaluate changes, in space and time, of areas occupied by coffee plantations in Minas Gerais. Land use maps of study areas selected in the main producing regions of the state were generated for the years 2000 and 2003 using the GIS SPRING and Landsat images. The results of the quantitative comparison of these maps indicated different behaviours for the regions evaluated. In São Sebastião do Paraíso and Machado, countries (south of Minas Gerais), a decrease of the areas occupied by coffee was observed, whereas in Três Pontas, increased. In Patrocínio, western part of the state, the area occupied by the crop remained unaltered. Remote sensing and GIS were efficient in the evaluation of the spatial-temporal dynamics of coffee lands of Minas Gerais, providing a greater understanding of the different environments and information that can support regional land use planning.